AgroMANAGER, a web application for farm management. (1st January 2011) - Bournaris, Thomas; Manos, Basil; Vlachopoulou, Maro; Manthou, Vicky
In this paper, we present the AgroMANAGER application. AgroMANAGER is a web-based application for farm management and particularly for organisation and administration of agricultural holdings. It is one of the main farm management applications of agroGOV.gr portal. The development of AgroMANAGER applications supports the farmer-manager in the difficult process of farm management and decision making. The objective of this application is to help the farmer-user, to gain control of the external environment with easy access to knowledge and information. AgroMANAGER provides to the farmer-manager management, administration and organisation services for the agricultural holdings. It is a simple system of keeping farm records and accounts to which farmers can monitor online the operation of their farms. It can provide a different approach to keeping accurate farm records and accounts and a helper in the difficult journey of agriculture of the future.